Assistance in applying sharia KUR financing as an alternative for MSME funding - Abdullah Syakur Novianto; Nanik Wahyuningtiyas; Tanzil Ilham; Ike Nurmaya Devina (Universitas Muhammadiyah Magelang, 2022)
Lack of capital and lack of knowledge about sharia-compliant financial products are the issues MSMEs in Kedungkandang Village are dealing with. Five stages make up the methodology employed for this program: socialization, counseling, training, mentoring, and monitoring and evaluation. The outcome of this program is that MSMEs in Kedungkandang Village understand the procedure for applying for financing to Islamic banks and can apply for sharia KUR financing to PT. Bank Syariah Indonesia, Tbk. as an alternative to funding.